Pendampingan Pembuatan Karya Tulis Ilmiah Bagi Mahasiswi Institut Darul Hadits Lil Irtsin Nabawi Tarim-Hadramaut Yemen - Musyarapah; Al-Adni, Yasir; Sardimi; Ahmadi; Dakir; Wahyudi, Rahmad; Karim, Haji Abdul; Pithriani (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
This article presents the results of an international community service program conducted collaboratively by faculty and students of the Master’s Program in Islamic Education Management at IAIN Palangka Raya. The program aimed to provide training and assistance in scientific writing at the Institut Darul Hadits Lil Irtsin Nabawi Tarim, Hadramaut, Yemen. The primary issue faced by the students at this institution was a lack of understanding of academic writing, due to the absence of relevant coursework. The objective of this assistance was to enhance the students' skills in preparing scientific papers. The program received positive and enthusiastic feedback from the institution's leadership and faculty. Results indicate that students still require further guidance on research methodology, word selection, and structuring academic papers. Such international community service programs can be implemented in various locations targeting students who need similar support and can benefit Islamic educational institutions at both national and international levels.